Septic shock upon admission to pediatric intensive care units: prognostic analysis of mortality in a retrospective cohort - Rodriguez-Portilla, Ricardo (2025)
Background: Septic shock is a common cause of admission to pediatric intensive care units (PICU) and is associated with significant mortality. Our objective was to analyze the association between septic shock diagnosis at PICU admission and mortality during hospitalization. Method: This retrospective cohort study was conducted in the PICU of Hospital Nacional Edgardo Rebagliati Martins (HNERM) in Lima, Peru, from January 2018 to December 2021. The sample size was determined based on annual mortality rates, and randomization was used to create two groups: patients with and without septic shock. To evaluate mortality risk, we performed a Poisson regression with robust variances and 95% confidence intervals (CI) using both crude and adjusted models. Results: Of 1,341 patients admitted to the PICU during the study period, 358 were included in the analysis. The study population was 51.9% female, with a median age of 3.7 years. The largest age group was children under 1 year, comprising 29.6% of participants. The septic shock group showed higher rates of mechanical ventila-tion requirement, longer hospital stays, and increased mortality. The risk of mortality was 2.73 times higher in patients admitted with septic shock compared to those admitted with other diagnoses (relative risks: 2.73; 95% CI: 1.36–5.46). Conclusion: Patients admitted to the PICU with septic shock demonstrated a 2.73 times higher risk of death compared to those admitted for other reasons.